Surgeons Opinions on Management of Normal Appendix during Laparoscopy for Right Iliac Fossa Pain - Tarhuni , Ashref; Elmehdawi , Haitham (Scientific Journal of University of Benghazi, 2024)
Right iliac fossa (RIF) pain is a common presentation in surgical emergencies, often leading to the diagnosis of acute appendicitis. However, the management of a normal appendix encountered during laparoscopic exploration for RIF pain remains debated among surgeons, with implications for patient outcomes and healthcare resources. This study aimed to assess the opinions of surgeons regarding the management of a normal appendix during laparoscopic surgery for RIF pain of uncertain etiology. A cross-sectional survey was conducted among 150 surgeons in Benghazi, yielding a 65.33% response rate. The survey collected demographic data, management opinions, and factors influencing decision-making regarding the removal of a normal appendix during laparoscopic procedures. The results showed that of the 98 respondents, approximately 80% reported that they routinely remove a normal appendix during laparoscopic surgery, primarily to prevent future appendicitis and avoid patient confusion. While most surgeons explained the risks and benefits of this decision to their patients, opinions varied on whether the decision should be made collaboratively. Notably, only 2% reported complications related to the removal of a normal appendix. The findings indicate a significant lack of consensus among surgeons concerning the management of a normal appendix during laparoscopic procedures. While many opt for routine removal, a substantial minority advocate for a more selective approach. The variability in practices highlights the need for clear, evidence-based guidelines to standardize care and optimize patient outcomes. This study underscores the heterogeneity in the management of normal appendices during laparoscopic exploration for RIF pain. Further research is necessary to develop definitive recommendations that can guide surgeons in clinical practice.